Incidental learning of second language vocabulary through extensive listening to the graded stories and authentic songs as well as watching authentic films by EFL Libyan learners - Almagrabi, Alarabi Abdelsalam Abdelnabi (2021)
This empirical study targeted Libyan undergraduates who studied at an English department in Libya. The present study aims to contribute to work in the field of second/foreign language acquisition, by investigating the extent foreign language (FL) vocabulary can be acquired incidentally through extensive exposure to authentic (songs and films) and non-authentic (simplified stories) spoken texts. Additionally, it will evaluate the extent to which the process leads to acquiring or enhancing vocabulary knowledge in terms of form recognition, meaning, grammatical behaviour and use. Based on the results, the two modes of spoken inputs (authentic and non-authentic) are compared to identify which is more effective for L2 vocabulary incidental learning. The incidental FL vocabulary learning was measured by means of Vocabulary Knowledge Scale (VKS) tests (pre-test, post-test and delayed-post-test). The present study contributes in the field of EFL/ESL through four different trends: firstly, it is the first study that targeted Libyan EFL learners of English as foreign language. Secondly, it is the first study that investigates incidental vocabulary learning of four knowledge aspects (form recognition, inferring meaning, grammar parts recognition, and word use). Thirdly, it is the first study that contrasts three different spoken inputs (listening to stories, listening to songs and watching films) with an aim to identify which of them leads to more vocabulary gains. Finally it is the first empirical study, to the best of my knowledge, that investigates the influence of five factors (frequency of occurrence, participants’ English language proficiency, participants’ previous vocabulary knowledge, participants’ vocabulary language strategies, and participants’ learning styles) which are hypothesized to play a crucial role in incidental vocabulary learning and to increase the likelihood of vocabulary being learnt from spoken input. In order to achieve the aims of the study, an experiment was designed and implemented. Two tests and two questionnaires were designed to investigate the five factors mentioned above. The outcomes of these two tests and two questionnaires were compared with the participants’ gains to evaluate the effects of those factors in incidental L2 vocabulary learning. The results revealed that vocabulary can incidentally be acquired through the extensive exposure to English stories, songs and films. Contrasting the three inputs demonstrates that the non-authentic materials (simplified stories) were more effective than authentic materials (songs and films) for L2 incidental vocabulary learning. The study also concluded that participants’ English language proficiency and their previous vocabulary knowledge affected the likelihood of incidental L2 vocabulary learning. It appears that the participants’ learning styles did not affect their L2 vocabulary learning as one would expect since learning styles is itself a contentious subject. As for the effect of frequency of occurrence, this study revealed that the effect of this factor on L2 vocabulary learning is weak unless some context clues exist in the oral texts. In terms of the influence of vocabulary language strategies the study concluded that this factor affected only the likelihood of incidental L2 vocabulary learning from films.